In-situ passivation mechanism of modified silicate composite biochar on soil cadmium. Issue 6 (December 2022) - Yuan, Shengnan; Zhang, Jinyu; Tan, Zhongxin
Abstract: Original biochar has the characteristic of fragile texture, which is easy to cause difficulties in application and environmental pollution during soil remediation. Moreover, it is difficult to be separated from the soil, the heavy metals passivated in-situ have the risk of being reactivated when the environment changes. Through the steps of "magnetization" and "granulation", modified silicate composite biochar was prepared and the fixation mechanism of the materials on cadmium was also explored. The results showed that: (1) The dry weight of wheat in the blank was only 0.062 g, as well as the dry weights treated by biochars were more than 0.117 g. The content of cadmium in wheat cultured with KM6 was 0.22 μg, only 39.64 % of the blank. (2) The biochar addition increased the soil's pH. The pH value of soil treated by silicate composite biochar reached 7.64–7.94, which promoted the transformation of cadmium ions to insoluble precipitation. (3) The content of available cadmium in untreated soil was 54.6 %, while which decreased to 22.9 %− 29.9 % after adding silicate composite biochar. (4) Magnetic biochar contained the special iron-containing structures and iron oxides, which can react with cadmium to form stable complexes (such as (FeO)2 Cd and (Fe-R-O)2 Cd) to promote the removal of heavy metals. Graphical Abstract: ga1 Highlights: The growth of wheat cultivated by biochar was better than that of the blank group. The cadmium content in wheat cultivated by KM6 was the lowest at 0.2171 μg. The increase of soil pH can also promote the insoluble precipitation of cadmium. The iron-containing structures in magnetic biochar contains can fix cadmium.